Optimalisasi Literasi Digital Untuk Meningkatkan Daya Saing UMKM di Desa Dolok Kahean - Firqin Fuad; Riyan Pradesyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program was carried out in Dolok Kahean Village, Tapian Dolok District, Simalungun Regency, with the main focus on optimizing digital literacy to increase the competitiveness of micro, small, and medium enterprises (MSMEs). The purpose of this program is to strengthen the competitive position of MSMEs, especially Rengginang Ibu Saliem, who still rely on conventional marketing systems and have a minimal understanding of business digitalization. The method used is a participatory and educational approach, carried out in four systematic stages: needs assessment, material design, program implementation, and mentoring and evaluation. The results of the activity showed significant achievements, with an increase in digital literacy understanding by 80% based on a comparison of pre-service and post-service. In practice, partners have succeeded in forming a business digital identity, namely @rengginanghuta_ibusaliem Instagram accounts, and are able to run digital marketing starting from content processes to customer interaction. Theoretically, these findings strengthen the argument that digital literacy is an essential foundation in facing the challenges of the digital economy, where increased competitiveness is not only influenced by technical skills, but also by changes in mindset and business independence. The implication of this program is that local MSMEs now have adequate capabilities and platforms to expand market reach beyond the village boundaries.